Rehabilitation of adult White offenders : an analysis of existing extra-institutional specialised services in the Republic of South Africa - Toussaint van Hove, Thea (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1962.